Implementasi Sistem Informasi Pengelolaan Keuangan Sekolah Di Smp Islam Khaira Ummah Padang Berbasis CodeIgniter - Nasution, Marsinah Dewi Feiyska; Hendriyani, Yeka (Universitas Negeri Padang, 2021)
Finance in school is a very important part because almost all school activities require money. Finance also needs to be regulated as well as possible, for that it needs good financial management. The financial management system available at Khaira Ummah Padang Islamic Middle School has not worked computerized or still uses conventional methods. Therefore, there needs to be other media as a means to help financial management become better. The purpose of this final project is to study, analyze, and design a school financial management information system at Khaira Ummah Padang Islamic Middle School. This information system is designed using the MVC (Model View Controller) architecture method. The tools used are Sublime Text as a text editor, PHP programming language, MySQL as database, Apache web server, and CodeIgniter framework. The final result of this design is a web-based information system that contains matters concerning school financial management at Khaira Ummah Padang Islamic Middle School.